Women's ILO : transnational networks, global labour standards, and gender equity, 1919 to present - Boris, Eileen, 1948-; Hoehtker, Dorothea, 1964-; Zimmermann, Susan (Studies in global social history, 2018)
Women's ILO examines a century-long history of women and their networks involved in and with the ILO, the gendered meaning of labour standards, and the challenges of achieving gender equity through international labour law, transnational campaigns, and local labour policies.--